Vergil 'disrobed': John Vicars' 'home-spun English gray-coat plain' Aeneid (1632). (11th May 2022) - Braund, Susanna
Abstract: This article puts the spotlight upon the neglected 1632 translation of the entire Aeneid by the poet, puritan, and parliamentarian John Vicars, which, as the first complete translation of the Aeneid by an Englishman, should be more prominent in literary history. The article's central argument is that the neglect of Vicars' translation was, both at the time and thereafter, a manifestation of the class warfare that has long pervaded English society. This argument complements the view expressed by other scholars that the dismissal of Vicars was grounded in his radical puritanism and anti-Catholicism. The article analyses the paratextual materials that introduce the translation, including the dedicatory epistle, the address to the reader, and the poems of endorsement, as well as the poem itself, for signs of class struggle. By offering a close textual analysis, it argues that it is far from obvious that the quality of Vicars' version is inferior. It concludes that the patent early hostility towards Vicars is more closely related to the person of the translator than the qualities of the translation; specifically, it attributes the failure of Vicars' translation to dislike for the translator's extremely humble origins, alongside his unfashionable religious and political views.